2007
DOI: 10.1089/end.2006.450
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Open Conversion of Laparoscopic Adrenalectomy: A 13-Year Review of 456 Cases

Abstract: Knowledge of tumor size, BMI, and tumor type can help in counseling patients undergoing laparoscopic adrenalectomy with regard to the probability of conversion. The size of the tumor was found to be the most important predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 36 publications
6
42
2
1
Order By: Relevance
“…The conversion rate is usually estimated at 1-5% and depends mostly on the experience of the surgeon and extent of surgery [5,7,8,11,[13][14][15]. In our material the number of conversions (2.91%) fell into this range.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The conversion rate is usually estimated at 1-5% and depends mostly on the experience of the surgeon and extent of surgery [5,7,8,11,[13][14][15]. In our material the number of conversions (2.91%) fell into this range.…”
Section: Discussionmentioning
confidence: 61%
“…This phenomenon is Table VI. Treatment of complications requiring surgical intervention often described in the literature [5,9,10,11,14,15]. More importantly, complication-driven conversions were reduced significantly, from 0.6% in the 1 st period to 0.27% and 0.26%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Laparoscopic adrenalectomy in morbidly obese patients may be technically demanding, and these patients are at increased risk for complications as well as higher chance for open conversion 18 . In our experience, we find that except for the extra efforts that are required on the part of the surgical team, the patient's health is not more…”
Section: Discussionmentioning
confidence: 99%
“…Even though contrary opinions have been advocated in the literature, higher body mass index is a risk factor necessitating conversion to open surgery. [24] Intraoperatively, histopathologically benign adrenal masses are more frequently encountered. In a series of 52 patients adrenalectomized by Zacharias et al [25] 34 patients with benign pathology had been reported.…”
Section: Discussionmentioning
confidence: 99%